Juvenile recurrent respiratory papillomatosis: A rare masquerade of asthma - Boo, WH (Malays Fam Physician, 2015)
Juvenile recurrent respiratory papillomatosis (JRRP) is a rare condition. The varied presentation of this condition predisposes to misdiagnosis and potential life-threatening airway obstruction. In this paper, we have reported a case of JRRP presenting as severe respiratory distress and consequently mistreated as asthmatic attack culminating in a near fatal acute airway obstruction.